Fighting recent inflation: An empirical literature review of monetary and governmental policies - Christof Haar (Managerial Economics)
Inflation is a crucial issue for businesses and households, central banks and governments, in fact for all economic actors, as it has a strong impact on economic growth and welfare. This literature review captures how monetary policy and governmental policy can control inflation, how their measures work, and which are the key points to consider when conducting these policies, especially in times of crisis. It uses academic papers from the past eight decades, supplemented by publications from financial and economic institutions, but focuses on literature beginning with the 2000s to capture the latest methods and techniques to find out what drives inflation and how. Monetary policy and governmental policy should act together to effectively fight inflation. Monetary policy can have adverse effects on governments’ future tax revenues and debt-to-GDP ratios. Fiscal policy measures should be associated with altered government spending to avoid high inflation rates and/or high debt burdens in the future. Especially during and right after crises, measures have to be evaluated as too long support can fuel inflation in the future. Both parties should also take into account people’s inflation expectations, as these shape their economic behaviour.